BAHASA ARAB KEISTIMEWAAN BAHASA ARAB SEBAGAI BAHASA AL QURAN: KEISTIMEWAAN BAHASA ARAB SEBAGAI BAHASA AL QURAN - Risna, Risna (Program Studi Bahasa dan Sastra Arab STAIN Majene, 2023)
This article examines the concept In the world of modern languages, there are no other languages ​​that outperform each other, but when viewed from a historical, cultural and linguistic point of view they can be superior to other languages. Arabic is one of the oldest languages ​​in the world, which has the privilege of being the language of the Koran by having beautiful structural rules. The preparation of Arabic grammar is part of the elements of the composition of the Qur'an which is one form of the miracles of the Qur'an. In this paper we try to present some of the features of the Arabic language in terms of its use in the Qur'an as well as from its historical aspects. This paper presents an understanding that Arabic has a specialty not only because it is used as the language of Muslims, but Arabic has another uniqueness in terms of its language.